Binding site feature description of 2-substituted benzothiazoles as potential AcrAB-TolC efflux pump inhibitors in E. coli - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
The resistance-nodulation-division (RND) family efflux pumps are important in the antibiotic resistance of Gram-negative bacteria. However, although a number of bacterial RND efflux pump inhibitors have been developed, there has been no clinically available RND efflux pump inhibitor to date. A set of BSN-coded 2-substituted benzothiazoles were tested alone and in combinations with ciprofloxacin (CIP) against the AcrAB-TolC overexpressor Escherichia coli AG102 clinical strain. The results indicated that the BSN compounds did not show intrinsic antimicrobial activity when tested alone. However, when used in combinations with CIP, a reversal in the antibacterial activity of CIP with up to 10-fold better MIC values was observed. In order to describe the binding site features of these BSN compounds with AcrB, docking studies were performed using the CDocker method. The performed docking poses and the calculated binding energy scores revealed that the tested compounds BSN-006, BSN-023, and BSN-004 showed significant binding interactions with the phenylalanine-rich region in the distal binding site of the AcrB binding monomer. Moreover, the tested compounds BSN-006 and BSN-023 possessed stronger binding energies than CIP, verifying that BSN compounds are acting as the putative substrates of AcrB.
Keywords: AcrAB-TolC; AcrB docking; benzothiazoles; ciprofloxacin; E.coli AG102; EPI; GRAM-NEGATIVE BACTERIA; ESCHERICHIA-COLI; MOLECULAR DOCKING; DRUG EFFLUX; ANTIMICROBIAL ACTIVITY; ANTIBIOTIC-RESISTANCE; CONTINUUM SOLVENT; TOPOISOMERASE-II; ACTIVE EFFLUX; FORCE-FIELD